2012
DOI: 10.1007/s00432-012-1169-3
|View full text |Cite
|
Sign up to set email alerts
|

Bone metastases in germ cell tumor patients

Abstract: Bone metastases were associated with a primary mediastinal nonseminoma, yolk sac histology, and liver metastases at first diagnosis. In this cohort of patients receiving HD-CTX as first-line treatment, 63% achieved long-term progression-free survival. Skeletal relapses were rare, but showed dismal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 19 publications
2
29
0
Order By: Relevance
“…Retrospective data from the German Testicular Cancer Study Group reported that 63% of NSGCT patients (including primary mediastinal cases) with bone metastases receiving HDCT as a first-line treatment achieved lasting progression-free survival. 18 Although important findings were observed, many potential biases resulting from the retrospective design of the analysis have to be considered. First, information on the decisionmaking process for selecting the first-line or second-line chemotherapy or marker-positive surgery is not available.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective data from the German Testicular Cancer Study Group reported that 63% of NSGCT patients (including primary mediastinal cases) with bone metastases receiving HDCT as a first-line treatment achieved lasting progression-free survival. 18 Although important findings were observed, many potential biases resulting from the retrospective design of the analysis have to be considered. First, information on the decisionmaking process for selecting the first-line or second-line chemotherapy or marker-positive surgery is not available.…”
Section: Discussionmentioning
confidence: 99%
“…Bone metastasis is also rare, constituting less than 1% of metastasis at the time of primary diagnosis or relapse [40]. However, it has been shown in patients specifically with poorrisk disease to constitute up to 9% [41]. In this study, Oechsle et al retrospectively reviewed40 patientswith bonemetastases from a cohort of 434 patients with poor-risk disease [41].…”
Section: Postchemotherapy Surgery For Sites Outside the Retroperitoneummentioning
confidence: 99%
“…However, it has been shown in patients specifically with poorrisk disease to constitute up to 9% [41]. In this study, Oechsle et al retrospectively reviewed40 patientswith bonemetastases from a cohort of 434 patients with poor-risk disease [41]. All patients underwent primary high-dose cisplatin-based chemotherapy with peripheral blood stem cell reinfusion.…”
Section: Postchemotherapy Surgery For Sites Outside the Retroperitoneummentioning
confidence: 99%
See 1 more Smart Citation
“…In one series including 19 patients with bone involvement (13 primary and 6 relapsed tumors) treated by conventional chemotherapy, no information on the further management of the bone lesions after initial chemotherapy was given [36]. In the largest series available which included 40 patients with primary bone metastases from germ cell tumors (all had non-seminomas) who underwent primary high-dose chemotherapy, long-term progression-free survival was achieved in 63% of patients [37]. In this study, the overall treatment response rate (85%) was identical in patients with and without metastatic bone involvement.…”
Section: Germ Cell Tumorsmentioning
confidence: 99%